Design and development of body electrical system and controller temperature control system for electric motorcycles - Kurniawan, Aldi; Setiadi, Rizki; Sumbodo, Wirawan; Naryanto, Rizqi Fitri (Universitas Negeri Semarang, 2025)
The rapid evolution of technology has transformed the automotive industry, transitioning from internal combustion engines to electric vehicles (EVs) to reduce greenhouse gas emissions and dependence on fossil fuels. This study focuses on developing a body electrical system for electric motorcycles by integrating components like lead-acid batteries, pulse-width modulation (PWM) controllers, waterproof DS18B20 temperature sensors, DC-DC converters, and energy-efficient LED lighting. The system is designed to comply with Indonesia’s National Standards (SNI). Employing the 4D research methodology (Define, Design, Develop, Disseminate), the electrical system underwent rigorous validation and testing. Results highlight enhanced performance, improved energy efficiency, and effective thermal management. The integration of a temperature control system reduced the risk of overheating, ensuring safety and operational reliability. This research contributes to advancing EV technology, offering a framework for optimizing body electrical systems for electric motorcycles in compliance with safety and performance standards